Hydration behaviors of calcium silicate-based biomaterials - Yuan-Ling Lee; Wen-Hsi Wang; Feng-Huie Lin; Chun-Pin Lin (Journal of the Formosan Medical Association, 2017)
Calcium silicate (CS)-based biomaterials, such as mineral trioxide aggregate (MTA), have become the most popular and convincing material used in restorative endodontic treatments. However, the commercially available CS-based biomaterials all contain different minor additives, which may affect their hydration behaviors and material properties. The purpose of this study was to evaluate the hydration behavior of CS-based biomaterials with/without minor additives. Methods: A novel CS-based biomaterial with a simplified composition, without mineral oxides as minor additives, was produced. The characteristics of this biomaterial during hydration were investigated using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectrometry. The hydration behaviors of commercially available gray and white MTAs with mineral oxide as minor additives were also evaluated for reference. Results: For all three test materials, the XRD analysis revealed similar diffraction patterns after hydration, but MTAs presented a significant decrease in the intensities of Bi2O3-related peaks. SEM results demonstrated similar porous microstructures with some hexagonal and facetted crystals on the outer surfaces. In addition, compared to CS with a simplified composition, the FTIR plot indicated that hydrated MTAs with mineral oxides were better for the polymerization of calcium silicate hydrate (CSH), presenting Si–O band shifting to higher wave numbers, and contained more water crystals within CSH, presenting sharper bands for O–H bending. Conclusion: Mineral oxides might not result in significant changes in the crystal phases or microstructures during the hydration of CS-based biomaterials, but these compounds affected the hydration behavior at the molecular level.